Penggunaan Diksi dan Kalimat Efektif Untuk Meningkatkan Kualitas Karya Ilmiah Mahasiswa - Waruwu, Yesika; Ndruru, Tobias Shanmorla; Sihombing, Hadriana; Prasetyo, Dimas; Andhika, Muhammad Rakha; Pulungan, Hendra Kurnia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Scientific writing is the main academic expression for students to convey ideas, research findings, and intellectual contributions. However, the quality of scientific papers often faces linguistic challenges, particularly in word choice (diction) and sentence construction. Inaccurate diction may lead to ambiguity, imprecise terminology, and an unprofessional impression. For instance, using the term “river water volume” instead of “river discharge” may reduce data validity and cause misunderstandings. In addition, lengthy and ineffective sentences hinder readers’ comprehension and contradict the characteristics of academic language, which should be concise, formal, and objective. This study employs a library research method by reviewing books, scientific articles, and language guidelines, as well as analyzing sample sentences from students’ academic writings. The findings reveal that accurate diction improves semantic precision, while effective sentences strengthen arguments and facilitate understanding. These results emphasize the importance of linguistic competence as a fundamental factor in academic writing. Students need to develop the habit of using academic vocabulary, conducting self-editing, and referring to references such as the KBBI and PUEBI, so that their scientific works not only meet formal requirements but also achieve high quality and contribute to the advancement of knowledge.